Prosociality and a Sociosexual Hypothesis for the Evolution of Same-Sex Attraction in Humans - Barron, Andrew B.; Hare, Brian (Frontiers in Psychology, 2020)
Human same-sex sexual attraction (SSSA) has long been considered to be an evolutionary puzzle. The trait is clearly biological: it is widespread and has a strong additive genetic basis, but how SSSA has evolved remains a subject of debate. Of itself, homosexual sexual behaviour will not yield offspring, and consequently individuals expressing strong SSSA that are mostly or exclusively homosexual are presumed to have lower fitness and reproductive success. How then did the trait evolve, and how is it maintained in populations? Here we develop a novel argument for the evolution of SSSA that focuses on the likely adaptive social consequences of SSSA. We argue that same sex sexual attraction evolved as just one of a suite of traits responding to strong selection for ease of social integration or prosocial behaviour. A strong driver of recent human behavioural evolution has been selection for reduced reactive aggression, increased social affiliation, social communication and ease of social integration. In many prosocial mammals sex has adopted new social functions in contexts of social bonding, social reinforcement, appeasement and play. We argue that for humans the social functions and benefits of sex apply to same-sex sexual behaviour as well as heterosexual behaviour. As a consequently we propose a degree of SSSA, was selected for in recent human evolution for its non-conceptive social benefits. We discuss how this hypothesis provides a better explanation for human sexual attractions and behaviour than theories that invoke sexual inversion or single-locus genetic models.